A study on the role of oxidative stress and protein kinase signalling in hyperglycaemia induced cardiac remodelling - Amtha, Nikhil (Department of Human Biology, 2024)
Background Almost one-third of all deaths in patients with uncontrolled diabetes mellitus and hyperglycaemia are due to cardiovascular diseases. Chronic exposure of the heart to hyperglycaemia leads to a maladaptation called pathological cardiac remodelling and occurs via oxidative stress due to excess production of reactive oxygen species (ROS). In the heart, ROS modulates cardiac differentiation, cardiomyocyte proliferation, and myocardial tissue growth via ROS-sensitive protein kinases such as the mitogen-activated protein kinase (MAPK). Although there are several different MAPKs, the p38 MAPKs are involved in cardiogenesis and implicated in stimulating myocyte apoptosis, hypertrophy, or even antiapoptotic effects. As such, the role of p38 MAPKs in diabetic cardiac remodelling, especially during cardiac development, remains unclear. This study aims to elucidate the effect of hyperglycaemia on the p38 MAPK signalling pathway in a cardiac developmental model. Methods Pluripotent mouse embryonic stem cells (mESCs) were differentiated in vitro into cardiaclike pulsatile embryoid bodies (EBs) using the hanging drop method. Once pulsatile, EBs were further cultured for 72 hours in either baseline (25mM) or high glucose (50mM) media or with the pro-oxidant hydrogen peroxide (100μM). Changes in EB morphology and beating characteristics were observed using transmitted light microscopy. Immunocytochemistry and fluorescence microscopy imaging was used to detect changes in biomarkers. The nuclear uptake of propidium iodide (PI) was used to evaluate cell viability, whereas the 5-ethynyl-1- deoxyuridine (EdU) assay was used to determine cell proliferation. Western blot was used to analyse protein expression. Results Treatment with hydrogen peroxide stunted EB growth and decreased EB diameter, consistent with the presence of oxidative stress. High glucose increased the number of pyknotic-like nuclei and reduced the number of EdU-positive nuclei. Furthermore, hyperglycaemia elevated the expression of phosphorylated p38 MAPK, without altering total p38 MAPK expression levels. Inhibition of p38 MAPK by SB203580 in high glucose attenuated the increased number of pyknotic-like nuclei in high glucose and enhanced the number of EdUpositive nuclei compared to high glucose alone. High glucose also reduced the expression of the mitochondrial fusion regulatory protein, optic atrophy-1 (OPA1), with the inhibition of p38MAPK in high glucose attenuating this effect. Conclusion Hyperglycaemia induced pyknotic-like phenomenon, suppressed the proliferation, and reduced mitochondrial fusion protein machinery of mESC-derived cardiac-like cells. These effects were likely triggered by a mild form of oxidative stress and involved the activation of p38 MAPK. The findings provide insights into the mechanisms underlying diabetic developmental cardiac remodelling and identify p38MAPKs as a potential therapeutic target.